Diagnostic Accuracy of Uterine Artery Doppler and Umbilical Artery Doppler Flow studies for Predicting IUGR - Rabia Wajid, Saira Zeeshan, Amna A. Cheema, Saniya Shabbir, Hina Masood, Mehwish Ilyas, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the diagnostic accuracy of Uterine artery and Umbilical artery Doppler flow studies in predicting Intrauterine growth restriction taking birth weight as gold standard. Patients and methods: It was a Cross Sectional validation Study conducted at Department of Obstetrics and Gynaecology, Lady Willingdon Hospital, Lahore from 1st January 2021 to 30th April 2022. The uterine and umbilical arteries were analysed using Doppler. The newborn's weight in grammes was recorded right after birth. Results: In the diagnosis of intrauterine growth restriction, uterine artery Doppler has showed a sensitivity of 66%, specificity of 96.4%, diagnostic accuracy of 89%, PPV of 84.6%, and NPV of 90.4%. Conclusion: Uterine and umbilical arteries combined the greatest sign for predicting IUGR is Doppler. Keywords: Uterine artery Doppler, Intrauterine growth restriction, Diagnostic accuracy, Umbilical artery Doppler,